SEMANTIC CHANGES IN ENGLISH WORDS: HISTORICAL AND MODERN PERSPECTIVES - Shirinboyeva Khilola Kholbek kizi (Modern American Journals, 2025)
This article explores how the meanings of English words have changed over time, analyzing both historical developments and current trends. Semantic change – the evolution of word meanings – is a central aspect of language development. These changes occur due to cultural shifts, technological progress, social change, and linguistic processes. The paper discusses core types of semantic change – broadening, narrowing, amelioration, pejoration, and semantic shift – and supports each with historical and modern examples. Tables are provided to offer a clear classification and analysis of semantic developments. The study highlights how understanding semantic change benefits linguists, educators, and learners in grasping both the richness and complexity of the English language.
Keywords: Semantic change, lexical shift, historical linguistics, broadening, narrowing, metaphor, English vocabulary